Intratracheal ectopic thyroid: a rare cause of upper airway obstruction - Ehsan Ullah, Sana; Muhammad Irshad Hussain; Faizan Muhammad (Journal of the Pakistan Medical Association, 2026)
Intra-tracheal thyroid is a rare ectopic thyroid disease. Presenting symptoms can mimic those of airway obstruction such as bronchial asthma. We report the case of a male patient who presented with airway obstruction due to thyroid ectopia and was misdiagnosed initially with bronchial asthma. After a correct diagnosis of intra-tracheolaryneal thyroid, the case was managed by excision. Surgery is the mainstay of treatment for patients with clinical signs of airway obstruction. We present our experience of his one-month follow-up after resection. Currently, the patient is free of symptoms. Keywords: Intra-tracheal thyroid, Ectopic thyroid, Airway obstruction.